Pengembangan Sistem Manajemen Sumber Daya Manusia Perusahaan Retail (Studi Kasus: PT. Ramayana Lestari Sentosa Tbk Malang) - Johan Andi Saputra; Achmad Arwan; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The success of a company influenced by human resources and information technology. Progress of information technology is helpful for giving convenience every company to manage their employee. The human resource management involve recruitment, selection, employee assessment, employee payroll, employee evaluation, employee mutation, promotion, demotion, training, and work termination. The current human resource management is not optimal, so that we need a technology which can help to resolve this problem. This technology is a human resource management system based on web to make the human resource management easier than before. The system development process uses waterfall method. The requirements engineering phase produced 72 functional requirement and 1 non-functional requirement. Then, the implementation uses CodeIgniter framework, PHP programming language and MySQL database. In the testing phase using unit testing, integration testing, validation testing, and compatibility testing. Unit testing produce 100% valid in 5 test cases. Integration testing produce 100% valid in 2 test cases. Furthermore, the validation testing produced 100% valid in 17 test cases. And compatibility testing result in valid status in 1 test case.